Outcome evaluation of climate-smart research on solar-powered irrigation in India - Shepherd, Keith D. (CGIAR Research Program on Water, Land and Ecosystems, 2020)
As part of an Outcome Evaluation of Climate-Smart Research on Solar-Powered Irrigation in India, a simulation model was constructed with the objective of developing a scenario-building model of the main factors influencing adoption, major costs, benefits and risks associated with solar-powered irrigation. The main focus of the evaluation was on the solar power as a remunerative crop (SPaRC) model, also known as KUSUM-C under the multibillion-dollar Kisan Urja Shakti evam Utthan Mahabhiyan (KUSUM) initiative of the Government of India. The main objectives of the simulation modeling component were to: (i) project income and environmental benefits of the SPaRC scheme over the next 20 years; (ii) identify variables to which benefits are particularly sensitive; (iii) run scenario analysis for different values of sensitive variables; (iv) pinpoint what further research or actions could help to enhance adoption and outcomes, and what variables should be closely monitored; and (v) provide a learning tool that can be used to compare what actually happens with projections over time and can be continuously updated.